POTENSI DAMPAK LINGKUNGAN PADA PROSES PRODUKSI LIQUID CRISTAL DISPLAY (LCD) KOMPUTER - Sirait, Marudut (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2016)
Abstract. The aim of this paper is to assess and evaluate the environmental impact during the manufacturing process of Liquid Cristal Display (LCD) monitor of personal computer. Life cycle assessment (LCA) is utilized to evaluate the environmental impact during the manufacturing of LCD. The environmental load is expressed by Eco indicator 99 method. The damage categories based on Eco Indicator 99 consist of 11 categories, carcinogenic, respiratory inorganic, climate change, ionizing radiation, ozone layer depletion, Eco toxicity acidification/eutrophication, land use, extraction of mineral, and extraction of fossil fuels. Furthermore the environmental load is divided by three categories, which are human health, damage of ecosystem and depletion of resources. Simapro software version 8 is applied to calculate the environmental load each component of LCD display personal computer product. Finally, the result showed that the largest environmental load during the manufacturing process of a LCD computer display is to human health, followed by damage of ecosystem and the depletion of resources. Also, PWB component part of LCD monitor has the largest contributor for degradation environmental performance during the manufacturing process of monitor LCD, following by production of metal and plastic.